2019
DOI: 10.1037/ccp0000384
|View full text |Cite
|
Sign up to set email alerts
|

Provider fidelity and modifications to cognitive processing therapy in a diverse community health clinic: Associations with clinical change.

Abstract: The purpose of this study is to examine associations between therapist adherence, competence, and modifications of an evidence-based protocol (EBP) delivered in routine clinical care and client outcomes. Method: Data were derived from a NIMH-funded implementationeffectiveness hybrid study of Cognitive Processing Therapy (CPT) for PTSD in a diverse community health center. Providers (n ϭ 19) treated clients (n ϭ 58) as part of their routine clinical care. Clients completed the PCL-S and PHQ-9 at baseline, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 69 publications
6
56
0
2
Order By: Relevance
“…Whereas adaptations are often characterized in opposition to fidelity (i.e., fidelity‐inconsistent adaptations), adaptations can also be fidelity‐consistent, driving increased client buy‐in, client engagement, and fit with the client's specific needs and circumstances (Stirman et al, 2015). In fact, observational ratings of greater fidelity (i.e., adherence and competence) and fidelity‐consistent adaptations have both been associated with improved client outcomes in trauma treatment, suggesting that fidelity and adaptation might both beneficially impact clinical outcomes (Marques et al, 2019). Future studies are needed to further examine whether the adaptation‐fidelity tension indeed represents a false dichotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas adaptations are often characterized in opposition to fidelity (i.e., fidelity‐inconsistent adaptations), adaptations can also be fidelity‐consistent, driving increased client buy‐in, client engagement, and fit with the client's specific needs and circumstances (Stirman et al, 2015). In fact, observational ratings of greater fidelity (i.e., adherence and competence) and fidelity‐consistent adaptations have both been associated with improved client outcomes in trauma treatment, suggesting that fidelity and adaptation might both beneficially impact clinical outcomes (Marques et al, 2019). Future studies are needed to further examine whether the adaptation‐fidelity tension indeed represents a false dichotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention developers and implementation researchers can work to optimize fit of EBPs for different contexts by first understanding how community therapists adapt EBPs. Despite the reality that EBPs are often adapted by community clinicians session by session, minimal research has identified the frequency, types, and predictors of EBP adaptations occurring within psychotherapy sessions during implementation as usual in community settings (Marques et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In that situation, it would be erroneous to simply conclude that the adaptation itself was the source of the poor performance of the treatment manual. Recent evidence suggests that both fidelity and adaptation may contribute to outcomes (Marques et al, ). Alternatively, an adaptation may not “hit the mark” and address the most central barriers to effectiveness.…”
Section: Components Of the Ideamentioning
confidence: 99%
“…On the one hand, there is an understanding that EBPs must be delivered with some level of fidelity (i.e., in a manner, that is, consistent with the design or intent of said EBP; Eke, Neumann, Wilkes, & Jones, ; Kendall & Frank, ; McKleroy et al, ; Stirman et al, ). On the other hand, there is growing recognition that adaptations to EBPs are not only common (Aarons et al, ; Chambers & Norton, ; Wiltsey Stirman et al, ), but may be essential to maximizing clinical effectiveness in certain settings and populations (Chambers, Glasgow, & Stange, ; Iwelunmor et al, ; Marques et al, ; Stirman et al, ). For example, adaptations may be crucial to reducing health disparities, especially if the unmodified EBP would be ineffective or otherwise inappropriate for use with a historically underserved population (Bernal & Domenech Rodríguez, ; Cabassa & Baumann, ).…”
Section: Introductionmentioning
confidence: 99%
“…Providers were trained in CPT as part of a National Institute of Mental Health-funded (NIMH K23 MH096029-­01A1) implementation-­effectiveness hybrid pilot study of CPT for PTSD (for detailed description of the study design, please see ref29). Briefly, the study evaluated the feasibility and acceptability of adapting the CPT manual to be linguistically, culturally and contextually appropriate for a low-­income, diverse community population.…”
Section: Methodsmentioning
confidence: 99%